PENGARUH PERMAINAN LARI ESTAFET TERHADAP KETERAMPILAN GERAK DASAR PADA SISWA KELAS IV SDN 105388 KUALA BALI - Sri Alvira; Khairul Usman; Winara; Putra Afriadi; Try Wahyu Purnomo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Basic movement skills are essential for elementary school students as they form the foundation for physical development and mastery of various physical activities. However, based on observations at SDN 105388 Kuala Bali, fourth- grade students' basic movement skills are still relatively low, particularly in running ability, motor coordination, and accuracy in passing the baton in relay races. Therefore, effective and enjoyable learning methods are needed to improve these skills. This study aims to determine the effect of relay races on the basic movement skills of fourth-grade students at SDN 105388 Kuala Bali. This study used a quantitative approach with an experimental method using a One Group Pretest–Posttest design. The study sample consisted of 18 students selected using a total sampling technique. Data were collected through a basic movement skills test covering both process and outcome aspects, as well as a running test based on the Indonesian Physical Fitness Test (TKJI). Data analysis was performed using a t-test. The results showed an improvement in students' basic movement skills after being exposed to relay races. Therefore, it can be concluded that relay races have a significant effect on improving fourth-grade students' basic movement skills.